Developing England's North The Political Economy of the Northern Powerhouse (Building a Sustainable Political Economy: SPERI Research & Policy, 2018)
This book explores the politics of local economic development in Northern England. Socio-economic conditions in the North - and its future prospects - have become central to national debates in the UK. The status of Northern regions and their local economies is intimately associated with efforts to 'rebalance' the economy away from the South East, London and the finance sector in the wake of the 2008 financial crisis. The contributors to this volume focus in particular on the coalition and Conservative governments' 'Northern Powerhouse' agenda. They also analyse associated efforts to devolve power to local authorities across England, which promise to bring both greater prosperity and autonomy to the deindustrialized North. Several chapters critically interrogate these initiatives, and their ambitions, by placing them within their wider historical, geographical, institutional and ideological contexts. As such, Berry and Giovannini seek to locate Northern England within a broader understanding of the political dimension of economic development, and outline a series of ideas for enhancing the North's prospects. 'A collection of chapters exploring the historical, territorial and structural reality of the political economy of the North. Packed with evidence, assembled with exemplary scholarship.' -Michael Moran, The University of Manchester, UK 'At last, a serious academic contribution to the Northern Powerhouse debate that takes on the agglomeraniacs and Treasury tinkerers both empirically and philosophically. This book represents a clarion call for a progressive, pan-Northern politics putting the North of England once again at the vanguard of economic and democratic reinvention.' -Ed Cox, IPPR North, UK 'This book offers new insights into the political economy of the North of England. The topics covered are wide-ranging - from science policy to economic development - but the common theme is the policy agendas needed to address the North-South divide (and why existing approaches have failed).' -Neil Lee, The London School of Economics and Political Science, UK 'This outstanding collection shines a much needed light on the political economy of Northern England. The contributors perform an exacting multi-dimensional critique of economic policy making, city-regional governance and the inequalities entailed by the current UK approach to regionalism and devolution.' -Jonathan Davies, De Montfort University, UK.